Primitive Neuroectodermal Tumor of the Uterus: A Case Report - Tzu-Chen Yeh; Kian-Mei Chong; Yu-Hung Lin; Hun-Shan Pan; Kok-Min Seow; Jiann-Loung Hwang; Lee-Wen Huang (Elsevier, 2005)
Objective: Primitive neuroectodermal tumors (PNETs) are a group of unusual malignancies arising in the bone and soft tissue. Pure uterine neuroectodermal tumors are rare. We report the first case of PNET arising from the uterus in our hospital. Case Report: A 52-year-old perimenopausal woman had multiple myoma and was regularly followed-up in our hospital. She suddenly developed lower abdominal pain without vaginal bleeding. Sonography revealed a pelvic mass measuring 10.7 × 6.8 cm with multiple myoma. The patient underwent tumor resection. There were multiple necrotic tumors on the uterus, bladder, broad ligaments, cardinal ligaments, and cul-de-sac. Final pathology revealed PNET because tumor cells were CD99 positive. Conclusion: PNETs belong to the Ewing's sarcoma family. They are closely related to malignant, small round-cell tumors of soft tissue and bones. They strongly express the glycoprotein p30/32 (CD99) on the cell membrane, which is encoded by the MIC2 gene. A translocation at t(11;22)(q24;q12) has been identified. PNETs are mostly recognized by the histologic characteristics of neural differentiation and immunohistochemical expression of at least two different neural markers. Uterine PNETs have a poor prognosis and, to date, there is no standard treatment. Total abdominal hysterectomy and bilateral salpingo-oophorectomy plus adjuvant chemotherapy or radiotherapy are recommended.